La cultura organizacional y su incidencia en el desempeño de la gestión en el gobierno regional de piura - De Lama Castillo, Marco Antonio (2016)
This academic research was conducted at the Regional Government of Piura - Av headquarters in San Ramon s / n Urb San Eduardo, District of Piura Province of Piura... The study sample was made with workers who work in this organization. The interesting study conducted allowed to know a weak organizational culture through different governments have been weakening. Through different instruments applied has been known that its members do not feel identifying your institution was learned that the poor distribution of the rooms has created a work environment that is not welcomed by them. It is concluded that the Regional Government of Piura - Headquarters without their senior officials realize is working with people focused on their individualistic needs and remunerative character and who are not identified. A good plan of continuous improvement will change the current concepts of identification, assessment, necessary preparation, improved working methods, fairness, opportunity for growth, being familiar concepts that are given through a reorganization in the state. Achieved this purpose will be a connection with the public making that the primary aim to promote regional development by promoting public and private investment and employment.